ASSESSMENT OF THE HORMONAL VALUE OF WOMEN WITH OVARIAN ENDOMETRIOMA - Oripova, F.; Khamdamov, B.Z. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Endometriosis affects approximately 10% (190 million) of women and girls of reproductive age worldwide. Access to diagnosis and timely treatment for endometriosis is important, but access to such services is limited in many countries, including low- and middle-income countries. Materials and methods. The examination data of 87 patients with endometriotic ovarian cysts (ECOC) aged from 25 to 37 years (average age 29.4±2.3 years) were analyzed. 55 (63.2%) women with the 2nd degree (average cyst diameter 3.9±1.2 cm) made up the 1st group and 32 women (36.8%) with the 3rd degree of the disease (above 5 .8 cm) made up the 2nd group. 20 somatically healthy women of the same age without reproductive health disorders formed the control group. The concentration of sex hormones (FSH, LH, prolactin, estradiol (on days 2-3 of the menstrual cycle) and progesterone (7 days before the start of the menstrual cycle) in peripheral blood serum was determined by enzyme-linked immunosorbent assay. Result. In patients with ovarian endometrioma, an increase in the level of estradiol and prolactin was found in comparison with the control group (p <0.001). The presence of ovarian endometriosis in patients does not hurt the state of the ovarian reserve. Conclusion. In patients with ovarian endometriosis, the biochemical parameters of the ovarian reserve do not have statistically significant differences in comparison with healthy patients.